A civil law review of shopee paylater default dispute resolution in Indonesia - Harry Qurba; Oktavianto Setyo Nugroho; Enjum Jumhana (Institute Of computer Science (IOCS), 2026)
The development of financial technology in Indonesia has driven the increasing use of credit-based digital payment services, one of which is Shopee PayLater. Although this service provides easy transactions and access to financing for the public, its use has also given rise to various legal issues, particularly related to default by users in fulfilling payment obligations. Previous research has generally focused on consumer protection aspects or the general mechanism of paylater services, while studies specifically analyzing default dispute resolution in the legal relationship between users and Shopee PayLater service providers are still limited. Therefore, this study aims to analyze the civil law review regarding default dispute resolution on Shopee PayLater in Indonesia and examine the forms of legal protection for the parties based on applicable laws and regulations. The research method used is normative juridical with a statutory approach and a conceptual approach. Data were obtained through a literature review sourced from the Civil Code, the Consumer Protection Law, the Electronic Information and Transactions Law, and the Financial Services Authority regulations regarding technology-based financial services. The results of this study indicate that the legal relationship between users and Shopee PayLater service providers constitutes a valid and binding electronic debt-receivable agreement based on the principle of freedom of contract as stipulated in Article 1338 of the Civil Code. Default by users results in legal consequences in the form of obligations to fulfill performance, payment of fines, and possible claims for damages. Dispute resolution can be carried out through non-litigation channels, such as negotiation, mediation, and payment restructuring, or through litigation in court. The novelty of this study lies in a comprehensive analysis of the legal construction of electronic agreements, default dispute resolution mechanisms, and legal protection for parties in the Shopee PayLater service as part of the fintech lending ecosystem. This research contributes to providing conceptual strengthening for regulatory development and improving public legal and financial literacy in the use of paylater services in Indonesia.